Uso del maní forrajero (Arachis pintoi) en la alimentación de bovinos de leche - Rovira Ojeda, Rebeca Zoraida (2022)
The purpose of this research is to analyze the benefits provided by the use of forage peanuts (Arachis pintoi) in the feeding of dairy cattle. The search for new food alternatives in cattle increases over the years, which is why some researchers have been tasked with conducting experiments including some types of forages to improve cattle performance. The use of legumes as a low-cost alternative to provide protein of high biological value is an attractive option in animal nutrition. This is why A. pintoi is considered an adaptable and high-quality forage source that could be a viable alternative to livestock systems in the tropics. This grass-related legume has shown great promise in terms of regenerative capacity during grazing and adequate meat and milk production in feeding systems using this legume. Forage peanuts are one of the legumes with the best quality and consumption by animals, since their protein content (16 to 20%) and minerals meet the requirements of livestock, with the exception of phosphorus. Arachis Pintoi improves the quality of the animals' diet, due to its high protein content. This stimulates the consumption of grass and improves the productive responses of the animals.